Comparison between methods of analysis for deflection of laterally loaded piles - Low, Siaw Mei (2007)
Deep foundation, which used extensively to support highway structures, machinery foundation, high rise building, etc are often subjected to both axial and lateral loads. To obtain a safe and economical design, the method adopted for design of lateral deflection must be appropriate. In this thesis, two different methods of analysis for the ground-line deflection of the single, elastic, free-head piles have been compared with the available test results obtained from full-scale instrumented test piles. The basis for comparison is on the variation in pile installation methods and types of soil in Malaysia. Two design methods were selected; one is the rational method of Broms and the other is a more rigorous method of Characteristic Load Method (CLM). From the results obtained, it is found that Broms’ method gives more conservative value (around 59% to 70% larger than measured value) of lateral deflection compared to CLM. Lateral deflections calculated using CLM were found to be in good agreement (around 2% to 24% larger than measured value) with values measured in field load tests.